Analysis of two different outbreaks in PICU of a tertiary care centre in two different time zones - Khan, Fatima; Tayyaba, Uzma; Sultan, Asfia; Akhtar, Anees; Ahmed, Shariq (International Journal of Human and Health Sciences (IJHHS), 2023)
Klebsiella pneumoniae is one of the common cause of nosocomial outbreak. With the emergence of multi-drug resistance, clinical management has become a serious challenge. The present study is a comparative analysis of changing trends of antimicrobial resistance (AMR) between two outbreaks of Klebsiella pneumoniae in PICU occurring over a gap of 8 years. Materials & Methods: 1054 Blood culture samples received from paediatric patients over a period of 6 months were tested by BacT/Alert-3D & VITEK-2 system. Survey of environmental samples was also conducted in Paediatric ICU. All the findings were then analysed with the data from another outbreak of MDR Klebsiella pneumoniae in PICU reported from the same institute in the year 2015. Result: From 154 (14.6%) positive paediatric blood samples, Gram-negative bacilli was most commonly isolated (75/154, 48.7%), followed by Gram-positive cocci (53, 34.4%). Amongst gram-negative isolates Klebsiella pneumoniae was commonest (40/75, 53.3%), followed by Pseudomonas speices (17.3%), Escherichia coli (16%), Burkholderia cepacia-complex (6.7%), and Acinetobacter baumanii-complex (4%). Out of 40 Klebsiella pneumoniae, 90% were extensively-drug resistant (XDR), i.e resistant to cephalosporins, carbapenems, aminoglycosides, fluoroquinolone, Co-trimaxazole as well as Tigecyclin. 45% of these patients were admitted in the PICU. However, previous outbreak reported 90 Klebsiella pneumoniae (43.3% of all isolates) over a period of 4 month, out of which 45.5% were MDR & 18.8% were ESBL producers. However, Carbapenems were effective in majority of them (98.9%), which is a contrast to our present finding (97.5% resistance). Moreover, multiple MDR strains of Klebsiella species (7/16 isolates, 43.7%) were obtained from PICU samples in previous outbreak, with antibiogram similar to that of patient samples. Similarly PICU sampling in the current outbreak also yielded XDR Klebsiella pneumoniae from medicine table, with similar profile that is seen in patients sample. Conclusion: On analysis of two outbreaks from same hospital in two different time zones, we observed changing trend in resistance pattern, as Carbapenems were effective in previously isolated MDR strains, but now XDR stains are isolated which are resistant to carbapenems as well. Urgent and effective measures are needed to restrain emergence and transmission of XDR strains within the hospital. Stringent infection control practices should be advocated and strictly followed. International Journal of Human and Health Sciences Supplementary Issue 02: 2023 Page: S119-S129